The effectiveness of corporate governance and audit quality on earnings management in Chinese public companies - Liu, Yan (2022)
The purpose of this research is to explore the effect of corporate governance and audit quality in mitigating earnings management. This study examines all A-share public companies in China as samples between 2016 and 2020. The ordinary least square (OLS) estimator with the control for the year and industry fixed effects is used in this paper to assess various factors which may affect discretional behaviours on earnings. According to the empirical results, corporate governance plays a crucial role in deterring earnings management. The increase of board size can effectively reduce earnings management. Financial manipulation also can be partially inhibited under the more independent board. Managerial shareholding and institutional shareholding have a positive impact on earnings management. However, regarding audit quality, apart from audit independence which can partially mitigate earnings management, audit size and tenure have no impact on preventing earnings manipulation in the Chinese market. In addition, other factors as control variables, including firm size, profitability, firm growth, and leverage, also have a certain impact on the level of earnings management.